2020
DOI: 10.46328/ijte.v3i2.26
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Audio-visual Social Media Resources-supported Instruction on Learning Outcomes in Reading

Abstract: Perennial poor performance in English language in public examinations has been linked to the proliferation of social media tools in the classroom. However, contrary to the general belief that social media hinders learning and distracts learners’ attention, this study attempted to improve the quality of instruction through social media-supported audio-visual resources in teaching reading comprehension. Pretest, posttest, control group, quasi-experimental research design was adopted for the study and participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…There is growing and convincing evidence that engaging in creative arts activities can promote improvements in perceived physical and mental health, social functioning and wellbeing in long-term conditions (Franklin, 2017;Fincher, 1991;Grewal, et al, 2019;Huss et al, 2015;Kaimal& Arslanbek, 2020;Kara, 2020b;Keefer & Haj-Broussard, 2020;Olagbaju & Popoola, 2020;Secker et al, 2017). It is sometimes argued that the richness of the personal visual imagination of people relates to the ability to create artistic / creative images (Pérez-Fabello & Campos, 2007;Yilmaz & Argun, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing and convincing evidence that engaging in creative arts activities can promote improvements in perceived physical and mental health, social functioning and wellbeing in long-term conditions (Franklin, 2017;Fincher, 1991;Grewal, et al, 2019;Huss et al, 2015;Kaimal& Arslanbek, 2020;Kara, 2020b;Keefer & Haj-Broussard, 2020;Olagbaju & Popoola, 2020;Secker et al, 2017). It is sometimes argued that the richness of the personal visual imagination of people relates to the ability to create artistic / creative images (Pérez-Fabello & Campos, 2007;Yilmaz & Argun, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, students who focus on specific tasks, such as reading frequently to practice or focusing on frequent words, will eventually develop high reading comprehension. Moreover, many studies (Chang & Millett, 2014;Olagbaju & Popoola, 2020;Rezaee, Farahian, & Mansooji, 2019;Webb & Chang, 2012) have revealed that using technology, such as audio-visual aids, will support reading comprehension and fluency. Thus, this study seeks to uncover the effects of using video and audio technology to support and improve students' reading comprehension and fluency.…”
Section: Context Of the Problemmentioning
confidence: 99%
“…Moreover, social media is defined more clearly as "a group of Internet-based applications that build on the ideological and technological foundation of Web 2.0 and allow creation and exchange of user-generated contents (Zgheib and Dabbagh, 2020). Mobile devices and social media provide students with opportunities to access resources, learning materials, and course content and to interact with tutors and peers (Greenhow and Lewin, 2016;Olagbaju and Popoola, 2020). Anderson and Jiang (2018) report that 95% of teenagers have access to a mobile device; furthermore, 45% state that they are "constantly online."…”
Section: Introductionmentioning
confidence: 99%